7(x-1)=-49

Simple and best practice solution for 7(x-1)=-49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-1)=-49 equation:


Simplifying
7(x + -1) = -49

Reorder the terms:
7(-1 + x) = -49
(-1 * 7 + x * 7) = -49
(-7 + 7x) = -49

Solving
-7 + 7x = -49

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 7x = -49 + 7

Combine like terms: -7 + 7 = 0
0 + 7x = -49 + 7
7x = -49 + 7

Combine like terms: -49 + 7 = -42
7x = -42

Divide each side by '7'.
x = -6

Simplifying
x = -6

See similar equations:

| cd=5 | | -3(x+3)=3 | | -3x^2+24x-17=0 | | -7(4+x)=7 | | 3(x-4)=42 | | 6(x-8)=12 | | -3(2-x)=12 | | log(1024)4=x | | 5x+82=9x-6 | | 3x^2+x-10=0 | | (3x+15)(x^2+10x+21)=0 | | 9-7x=123-28x | | N^2+7n+6=0 | | 2(8+x)=22 | | 12=2x^2+5x | | -3(2s-5)-15=-3(7s+5)-3 | | 2(8+1)=22 | | 5q^2+18q=8 | | k^2-3k-10=0 | | 3x+2=81 | | (-x+9)(x-5)=0 | | 16y=2 | | 10=6(a-7) | | 2x-5=7x-30 | | 3a^2x^2+2ax=7 | | -16t^2+64t+64=0 | | 6+3(x-5)=2(x-3) | | 2x^2-8x+7=0 | | -7(4x-1)+8=-28x+15 | | -7(4x-1)+8=-25x+15 | | x+6=-4x+106 | | 5x*2-8x-4= |

Equations solver categories